2020
DOI: 10.1093/ehjqcco/qcaa081
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular comorbidities as predictors for severe COVID-19 infection or death

Abstract: Background Pre-existing cardiovascular diseases (CVDs) have been proposed to identify patients at higher risk of adverse COVID-19 outcomes, but existing evidence is conflicting. Thus, it is unclear whether pre-existing CVDs are independently important predictors for severe COVID-19. Methods and results In a nationwide Danish cohort of hospital-screened COVID-19 patients aged > =40, we investigated if pre-existing CVDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 29 publications
(36 reference statements)
4
40
0
1
Order By: Relevance
“…11,19,33,34 In addition to older age, prior work has documented evidence of increased risk for COVID-19 infection, severity, and/or fatality among patients with certain symptoms, preexisting medical conditions, and abnormal laboratory findings. 4,7,13,14,28 Although the significance and magnitude of associations varied between studies, our finding of declining mortality seems to support the idea of greater risk for severe or fatal disease among patients that have these risk factors. In our study, patients hospitalized in March compared to later months had more exacerbating symptoms (e.g., fever, dyspnea, cough) and evidence of biomarkers on inflammation, infection, cardiac and muscle injury, decreased liver and kidney function.…”
Section: Frequency Of Covid-19 Infection Among All Vha Userssupporting
confidence: 50%
See 3 more Smart Citations
“…11,19,33,34 In addition to older age, prior work has documented evidence of increased risk for COVID-19 infection, severity, and/or fatality among patients with certain symptoms, preexisting medical conditions, and abnormal laboratory findings. 4,7,13,14,28 Although the significance and magnitude of associations varied between studies, our finding of declining mortality seems to support the idea of greater risk for severe or fatal disease among patients that have these risk factors. In our study, patients hospitalized in March compared to later months had more exacerbating symptoms (e.g., fever, dyspnea, cough) and evidence of biomarkers on inflammation, infection, cardiac and muscle injury, decreased liver and kidney function.…”
Section: Frequency Of Covid-19 Infection Among All Vha Userssupporting
confidence: 50%
“…In our study, patients hospitalized in March compared to later months had more exacerbating symptoms (e.g., fever, dyspnea, cough) and evidence of biomarkers on inflammation, infection, cardiac and muscle injury, decreased liver and kidney function. 4,7,13,14,28 Additionally, we found that both hospitalized and deceased patients had more underlying comorbidities in March compared to later months including severe cardiovascular diseases, diabetes, renal disease, and obesity. However, deceased patients had a higher frequency of such comorbidities.…”
Section: Frequency Of Covid-19 Infection Among All Vha Usersmentioning
confidence: 72%
See 2 more Smart Citations
“…The poor outcomes for COVID 19 related to the cardiovascular co-morbidities may be a direct result of the condition itself or attributed to other conditions [ 34 ]. Some authors have found rather modest associations of adverse outcomes and hypertensive comorbidities like Atkins JL et.al.…”
Section: Discussionmentioning
confidence: 99%